Pendampingan dan Pelatihan Sertifikasi Halal: Pilar Keberlanjutan UMKM di Sektor Pangan - Dicky Wisnu Usdek Riyanto; Viajeng Purnama Putri (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Effective assistance involves various certification bodies and related stakeholders. The training was held to increase wet cake entrepreneurs' understanding of halal certification requirements, the implementation process, and the long-term benefits. The sustainability of wet cake entrepreneurs in the food sector is reflected in their ability to meet the demands of consumers who are increasingly aware of the halalness of their products. In the context of globalization, halal certification is not only an obligation, but also the key to access to international markets. This article provides insight into how implementing halal certification through mentoring and training can open up new opportunities for MSMEs to compete and survive in global competition. By strengthening this pillar of sustainability, MSMEs in the food sector can play a more active role in supporting local economic growth and improving the image of the Indonesian food industry in the eyes of the world.